Loss of Function of mtHsp70 Chaperone Variants Leads to Mitochondrial Dysfunction in Congenital Sideroblastic Anemia - Vishwanathan, Vinaya; D’Silva, Patrick (Frontiers in Cell and Developmental Biology, 2022)
Congenital Sideroblastic Anemias (CSA) is a group of rare genetic disorders characterized by the abnormal accumulation of iron in erythrocyte precursors. A common hallmark underlying these pathological conditions is mitochondrial dysfunction due to altered protein homeostasis, heme biosynthesis, and oxidative phosphorylation. A clinical study on congenital sideroblastic anemia has identified mutations in mitochondrial Hsp70 (mtHsp70). Mitochondrial Hsp70 plays a critical role in maintaining mitochondrial function by regulating several pathways, including protein import and folding, and iron-sulfur cluster synthesis. Owing to the structural and functional homology between human and yeast mtHsp70, we have utilized the yeast system to delineate the role of mtHsp70 variants in the etiology of CSA’s. Analogous mutations in yeast mtHsp70 exhibited temperature-sensitive growth phenotypes under non-respiratory and respiratory conditions. In vivo analyses indicate a perturbation in mitochondrial mass and functionality accompanied by an alteration in the organelle network and cellular redox levels. Preliminary in vitro biochemical studies of mtHsp70 mutants suggest impaired import function, altered ATPase activity and substrate interaction. Together, our findings suggest that the loss of chaperone activity to be a pivotal factor in the pathophysiology of congenital sideroblastic anemia.